LEFT-VENTRICULAR MAXIMAL SYSTOLIC ELASTANCE CALCULATED BY A COMBINATION OF M-MODE ECHOCARDIOGRAPHY AND STANDARD MANOMETRY - Matsubara, Beatriz Bojikian [UNESP]; Bregagnollo, E. A.; Ribeiro, MACL; Tucci, PJF (Associação Brasileira de Divulgação Científica (ABRADIC), 1991)
1. A method for obtaining the end-systolic left ventricular (LV) pressure-diameter and stress-diameter relationships in man was critically analyzed.2. Pressure-diameter and stress-diameter relationships were determined throughout the cardiac cycle by combining standard LV manometry with M-mode echocardiography. Nine adult patients with heart disease and without heart failure were studied during intracardiac catheterization under three different conditions of arterial pressure, i.e., basal (B) condition (mean +/- SD systolic pressure, 102 +/- 10 mmHg) and two stable states of arterial hypertension (H(I), 121 +/- 12 mmHg; H(II), 147 +/- 17 mmHg) induced by venous infusion of phenylephrine after parasympathetic autonomic blockade with 0.04 mg/kg atropine.3. Significant reflex heart rate variation with arterial hypertension was observed (B, 115 +/- 20 bpm; H(I), 103 +/- 14 bpm; H(II), 101 +/- 13 bpm) in spite of the parasympathetic blockade with atropine. The linear end-systolic pressure-diameter and stress-diameter relationships ranged from 53.0 to 160.0 mmHg/cm and from 97.0 to 195.0 g/cm3, respectively.4. The end-systolic LV pressure-diameter and stress-diameter relationship lines presented high and variable slopes. The slopes, which are indicators of myocardial contractility, are susceptible to modifications by small deviations in the measurement of the ventricular diameter or by delay in the pressure curve recording.
Keywords: PRESSURE-DIAMETER RELATIONSHIP; STRESS-DIAMETER RELATIONSHIP; LEFT VENTRICULAR MAXIMAL ELASTANCE